2015
DOI: 10.1108/f-09-2014-0076
|View full text |Cite
|
Sign up to set email alerts
|

Does student satisfaction with school facilities affect exam results?

Abstract: Purpose – The purpose of this paper is to investigate the relationship between student satisfaction with school facilities and exam results. Design/methodology/approach – The authors combined exam results in Norwegian lower secondary schools with results from a nationwide, mandatory and annual survey that measures student satisfaction over a five-year period. The data were analyzed using regression methods (ordinary least squares and fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 18 publications
1
31
0
2
Order By: Relevance
“…The question of the positive and negative effects of school design on academic outcomes has been studied by a lot of researchers. Their efforts have revealed a modest relationship between students' exam results and their subjective satisfaction with the condition of their facilities (Hopland and Nyhus 2015). What is not clear is which aspects of school facilities these pupils are taking into account.…”
Section: Introductionmentioning
confidence: 99%
“…The question of the positive and negative effects of school design on academic outcomes has been studied by a lot of researchers. Their efforts have revealed a modest relationship between students' exam results and their subjective satisfaction with the condition of their facilities (Hopland and Nyhus 2015). What is not clear is which aspects of school facilities these pupils are taking into account.…”
Section: Introductionmentioning
confidence: 99%
“…Poor facilities may thus have a negative impact on the quality of public services. The education sector has received particular attention, see, e.g., Green and Turrell (2005), COSLA and the Scottish Government (2009), Lavy and Bilbo (2009), Kristoffersen and Larsen (2010), Hopland (2012;2014a), and Hopland and Nyhus (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Lavy & Bilbo (2009) studied facilities maintenance practices in large public schools in the State of Texas by analyzing how facilities maintenance is planned, managed and carried out by such schools and concluded that poor quality of facilities maintenance management practice existed in large public schools in Texas. Whereas, Hopland and Nyhus (2015) found that there is a relationship between satisfaction with school facilities and students' exam results. This underscores the importance of efficient FM services in schools.…”
Section: Literature Reviewmentioning
confidence: 95%